The Relationship between Preschool Children's Numeracy Literacy Ability and Readiness for Primary School in Turen District - Aisyatun Nabilla; Eny Nur Aisyah; Rosyi Damayani Twinsari Maningtyas (Jurnal CARE (Children Advisory Research and Education), 2026)
Numeracy literacy is a crucial factor in shaping logical thinking skills; however, research quantitatively linking numeracy literacy to preschool children's school readiness—particularly within a local context—remains limited. These skills, which encompass number recognition, counting, and pattern comprehension, form the foundation for a child's readiness to enter primary school. This study aimed to determine the relationship between preschool children's numeracy literacy skills and their level of readiness for primary school. A quantitative approach with a cross-sectional correlational design was employed, involving 94 parents of children in "Group B" (the oldest preschool cohort) in Turen District, selected via simple random sampling. Data were collected using a closed-ended, Likert-scale questionnaire measuring numeracy literacy and school readiness—covering cognitive, socio-emotional, motor, and independence aspects—and were subsequently analysed using the Pearson correlation test in SPSS. The results indicated that the children's numeracy literacy and school readiness fell into the moderate category. The Pearson correlation test revealed a strong, significant positive relationship between numeracy literacy and readiness for primary school (r = 0.634; p < 0.05). These findings underscore the importance of targeted, continuous early numeracy literacy stimulation in supporting children as they prepare for the transition to primary school.